Early Natural Menopause Is Associated With Poor Lung Health and Increased Mortality Among Female Smokers. Issue 5 (May 2023) - Zhai, Ting; Diergaarde, Brenda; Wilson, David O.; Kang, Huining; Sood, Akshay; Bayliss, Samuel H.; Yuan, Jian-Min; Picchi, Maria A.; Lan, Qing; Belinsky, Steven A.; Siegfried, Jill M.; Cook, Linda S.; et al.
ABSTRACT: Menopause results from the decline of estrogen levels and is driven by ovarian aging. Some tissues, including the lung, may contribute to local estrogen synthesis in the postmenopausal state. Cigarette smoking is the most established factor for early menopause, and previous studies have shown that the menopause transition accelerated age-related decline of lung function following a restrictive disease pattern. In addition, studies have supported a potential synergistic effect of cigarette smoking and menopause on lung function. Delineating the effect of menopause timing and estrogen exposure on subsequent disease development may have important benefits for health maintenance and disease prevention in older women. This study aimed to assess the associations between early menopause and lung biomarkers, lung cancer risk, and cause-specific mortality. Data were obtained from the Pittsburg Lung Screening Study, a community-based research cohort of current and former smokers screened with low-dose computed tomography (CT) at baseline and 1 year later. Menstrual and reproductive history and data on respiratory symptoms were collected through questionnaires. Radiographic emphysema score was calculated from the baseline CT scan. Early menopause was defined as age at menopause of <45 years. The study cohort included female Pittsburg Lung Screening Study participants who reported natural (n = 1038) or surgical (n = 628) menopause at study entry. A total of 1064 participants (63.9%) were current smokers with an average pack-years of 46.1 ± 19.8 at baseline. Early menopause was associated with several pathologies including self-reported wheezing (odds ratio [OR], 1.65; 95% confidence interval [CI], 1.18–2.30; P < 0.01), chronic bronchitis (OR, 1.73; 95% CI, 1.19–2.53; P < 0.01), cardiovascular diseases (OR, 1.87; 95% CI, 1.13–3.11; P = 0.02), radiographic emphysema (OR, 1.70; 95% CI, 1.25–2.31; P < 0.001), and incident airway obstruction (OR, 2.02; 95% CI, 1.03–3.96; P = 0.04) in women with natural menopause, but not surgical menopause except for physician-diagnosed cardiovascular diseases (OR, 4.03; 95% CI, 1.78–9.14; P < 0.001). Trend tests for each of these outcomes in women with natural menopause identified monotonically increasing risk associated with younger age at menopause. Early menopause was associated with lower measurements of the lung function measurements forced expiratory volume in 1 second (FEV1 ; −104.8 ± 36.7 mL/s; P < 0.01), forced vital capacity (FVC; −78.6 ± 38.2 mL; P = 0.04), and FEV1 -to-FVC ratio (−2.1% ± 0.8%; P = 0.01) at baseline in women with natural menopause but not surgical menopause. The use of hormone therapy at any point was associated with higher baseline FEV1 levels and higher FEV1 -to-FVC ratio at baseline among women with natural menopause. Early natural menopause was associated with a 40% increased risk of all-cause death with respiratory diseases (hazard ratio [HR], 2.32; 95% CI, 1.52–3.52; P < 0.001), and early menopause was associated with twice the risk of lung cancer-specific mortality (HR, 1.94; 95% CI, 1.05–3.58; P = 0.03). This association was exacerbated by continuous cigarette smoking, with HRs of 4.65 (95% CI, 2.55–8.49; P < 0.001) and 4.61 (95% CI, 2.63–8.07; P < 0.001) for lung cancer and cancer mortality, respectively, among continuous smokers with early menopause compared with women with noncontinuous smoking and nonearly menopause. The results of this study demonstrate that among a postmenopausal cohort of middle-aged and older smokers, natural early menopause is associated with worse lung health and accelerated lung aging.